Greening negative factors in the activities of enterprises and organizations - Ye. E. Smirnova; M. Yu. Slesarev (Vestnik MGSU)
Introduction. Environmental certification in accordance with ISO 14001 and EMAS makes it possible to understand and assess the impact of economic activities on ecosystems, as well as to set environmental goals and objectives for improving the activities of enterprises and organizations. The effects of the EMS (environmental management and audit scheme) depend on how companies decide to use them after certification. In this regard, the authors investigate the organizational climate issues associated with the use of ISO 14000 and EMAS series standards to improve the environmental efficiency of companies.Materials and methods. The methodology is presented in the form of an environmental safety model related to the enterprises and organizations, including environmental audit, environmental standardization and environmental assessment of compliance with various environmental requirements at different levels of organization of enterprises’ activities. The object of research is the international environmental standards of the ISO 14000 and EMAS series. The subject of the study is the environmental safety of negative factors in the activities of enterprises and organizations. The concept of the necessity of greening personnel training and a positively environmentally oriented organizational climate in enterprises and organizations is proposed.Results. The implementation of EMS does not always lead to an improvement in the environmental performance of companies. Some companies focus on formal criteria without taking into account real environmental problems. In addition, environmental indicators can take the form of coefficients and can be improved with unchanged or even worsened environmental impact. The organizational climate is important for the realization of EMS goals, especially the attitude of employees to the environment and environmental values. Despite limitations, EMS, environmental audit and ISO 14000 principles can help companies reduce their negative impact on the environment and increase their competitiveness, as well as make more informed choices when planning their activities.Conclusions. The importance of creating an organizational climate for the successful greening of negative factors in the activities of enterprises and organizations is emphasized. There is also a need for a more accurate assessment of the effectiveness of environmental measures when formulating environmental standards and assessing compliance with their implementation.